Agent-Based Simulation Of Crowd At The Tawaf Area. - Sarmady, S.; Haron, F.; Talib, Abdullah Zawawi (2007)
Every year during the Hajj season there is a concentration of more than two million people within the vicinity of the Masjid Al-Haram. Congested areas, such as the tawaf,, may reach beyond a safe level of four people per square meter during this peak period. The Tawaf area together with the Ottoman construction is able to accommodate up to 72,000 people (in a praying position). Simulation of the movement and behavior of such a huge crowd can be useful in managing this important event. One of the recent trends in modeling and simulation is the agent technology which has been used to model and simulate various phenomenon such as the study of land use, infectious disease modeling, economic and business study, urban dynamic and also pedestrian modeling. In this paper we use multi-agent based method to simulate the crowd at the Tawaf area. We present the architecture of the software platform which implements our proposed model and briefly report our early experience in using- Repast J which is an agent-based simulation toolkit to model the crowd at the area.